2016
DOI: 10.1007/s10157-016-1265-9
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exposure to high-fat and high-fructose diet evokes hypoadiponectinemia and kidney injury in rat offspring

Abstract: Our present study suggests that exposure to maternal HFF-diet during fetal and early postnatal development induces hypoadiponectinemia in offspring, which might cause renal injury and metabolic derangements later in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…However, limited data are available at present on the effects of maternal fructose consumption on the BP of adult offspring. Studies listed in Table 1 indicate that consumption of HF alone or as a part of diet by rodent mothers induces programmed hypertension in adult offspring [26,27,28,29,30,31,32,33]. We found that adult offspring of mothers exposed to 60% HF diet during pregnancy and lactation developed hypertension [26], which is consistent with the results of earlier studies involving fructose-fed adult rats [16,19].…”
Section: Effect Of Maternal Fructose Consumption On Programmed Hypsupporting
confidence: 90%
“…However, limited data are available at present on the effects of maternal fructose consumption on the BP of adult offspring. Studies listed in Table 1 indicate that consumption of HF alone or as a part of diet by rodent mothers induces programmed hypertension in adult offspring [26,27,28,29,30,31,32,33]. We found that adult offspring of mothers exposed to 60% HF diet during pregnancy and lactation developed hypertension [26], which is consistent with the results of earlier studies involving fructose-fed adult rats [16,19].…”
Section: Effect Of Maternal Fructose Consumption On Programmed Hypsupporting
confidence: 90%
“…This review will primarily be limited to MetS-related phenotypes induced by HF consumption in early life in rodent animal models, some of which are listed in Table 1 . Despite fructose alone can alter fetal programming to induce numerous features of MetS [17] , [18] , [19] , [23] , [25] , [26] , [28] , [29] , [30] , some animal studies have often used fructose as a part of diet along with salt [20] , [24] or fat [27] .…”
Section: Effects Of Maternal Fructose Consumption On Developmental Prmentioning
confidence: 99%
“… Types of fructose intake Species Phenotypes related to MetS Age at evaluation Ref. 10% w/v fructose in drinking water throughout lactation Male Sprague–Dawley rats Obesity, insulin resistance 8 weeks [23] 10% w/v fructose plus 4% NaCl in drinking water 28 days before conception and throughout gestation and lactation Male Sprague–Dawley rats Hypertension 9 weeks [24] 60% HF diet throughout pregnancy and lactation Male and female Sprague–Dawley rats Hypertension 3 months [14] , [15] , [17] , [19] 60% HF diet throughout pregnancy and lactation Male Sprague–Dawley rats Hypertension, insulin resistance, dyslipidemia 3 months [16] 60% HF diet throughout pregnancy and lactation plus 1% NaCl in drinking water from weaning to 3 months of age Male Sprague–Dawley rats Hypertension 3 months [20] 60% HF diet throughout pregnancy and lactation Male Sprague–Dawley rats Bladder dysfunction 3 months [18] 10% w/v high fructose corn syrup (HFCS-55) in drinking water throughout pregnancy and lactation Male and female Sprague–Dawley rats Adiposity, dyslipidemia 3 months [25] 10% w/v fructose in drinking water throughout gestation Male Sprague–Dawley rats Insulin resistance 3 months [26] 56.7% HF/high-fat diet throughout pregnancy and lactation Male Sprague–Dawley rats Hypertension, hyperglycemia, kidney disease 4 months [27] 60% HF diet throughout pregnancy and lactation Male Sprague–Dawley rats Dyslipidemia, hepatic steatosis 5 months [28] ...…”
Section: Effects Of Maternal Fructose Consumption On Developmental Prmentioning
confidence: 99%
See 1 more Smart Citation
“…AdipoR2 is primarily expressed in the liver and weakly expressed in the kidney, and mediates the activation of peroxisome proliferator-activated receptor α ( 5 , 11 13 ). Studies have demonstrated that AdipoR1 protects the kidney against inflammatory, fibrotic or oxidative damage through the activation of AMPK ( 14 19 ).…”
Section: Introductionmentioning
confidence: 99%